Empathetic Leaders: Cultivating Success Through Multifaceted Support and Continuous Growth - Indrayani, Sari; Hariri, Hasan; Riswandi, Riswandi; Handoko, Handoko (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aims to explore the interconnected roles of mentoring, coaching, modeling, and supervision in supporting personal and professional development. A systematic literature review was conducted, sourcing 29 articles to clarify definitions, roles, and distinctions among these frameworks. Through mentoring, individuals gain structured guidance; coaching fosters self-discovery; modeling provides behavioral examples; and supervision ensures adherence to ethical standards. The results reveal unique and overlapping functions of these roles, especially emphasizing coaching supervision’s value in maintaining quality and ethical practices. This study’s novelty lies in its comprehensive integration of these concepts within a single framework, highlighting synergies that enhance developmental outcomes. Consequently, this work contributes to the field by offering a holistic approach for practitioners to optimize human potential across educational and professional contexts.